The effect of Basic Oxygen Furnace, Blast Furnace, and Kanbara Reactor Slag as Reinforcement to Cement Based Mortar - Andrie Harmaji; Andri Hardiansyah; Neneng Annisa Widianingsih; Rodulotum Minriyadlil Jannah; Syoni Soepriyanto (JPSE (Journal of Physical Science and Engineering), 2022)
Slag is a waste from steelmaking industries that was released into the environment. Slag was used as reinforced material in mortar. Different types of slag, including Air Cooled Slag (ACS), Granulated Blast Furnace Slag (GBFS), Basic Oxygen Furnace Slag (BOFS), and Kanbara Reactor Slag (KRS), were used as a reinforcing material in this study. The composition of slag in the mixture on mortar was 10%, 20%, 30%, 40%, and 50%. The sample was made with a water-cement ratio (w/c) of 0.35, with the ratio of sand and cement being 1:1.5, respectively. Treatment of mortar sample at ambient temperature was applied. The mortar samples were left to cure until 3, 7, and 28 days, which performed a compression test. The results show that adding slag to the mortar enhanced the compressive strength of the pristine mortar. The highest strength was obtained by adding 10% slag at 28 days. The compressive strength of GBFS, BOFS, KRS, and ACS was 23.76 MPa, 23.28 MPa, 19.68 MPa and 17.48 MPa, respectively. Based on the XRD result, it was discovered that the mixture has more Calcium Silicate Hydrate Peak than Pristine mortar.DOI: 10.17977/um024v7i12022p056